PELATIHAN POSTING BUKU BESAR, PERANCANGAN NERACA SALDO, DAN PENYUSUNAN KERTAS KERJA BAGI SISWA/I SMA ST.KRISTOFORUS 1 - Ferry Adang; Cindy Tanujaya; Florencia May (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Financial statements are the main indicator of the success of a company in carrying out its commercial activities. The development of business activities and complexity that occurred in the era of the industrial revolution 4.0 requires a profession that has expertise in compiling and presenting standard financial reports in accordance with Financial Accounting Standards. Knowledge of the accounting profession is important for high school students who want to pursue work after high school education or can also be a provision of knowledge when continuing their education in higher education. This activity is a Community Service (PKM) which is carried out by providing benefits in the form of basic knowledge and expertise about accounting science in the process of posting ledgers and preparing trial balances in the accounting cycle given to students of SMA Kristoforus 1 located in the Grogol area. Activities will be carried out in the form of theoretical presentations and discussion of case questions which are simulations of the accounting process in the real world, specifically in the aspects of the process of posting the general ledger and preparing the trial balance, as well as with online interactive discussions. SMA St.Kristoforus1 is currently experiencing limited time due to the large amount of material presented in accordance with the existing curriculum. Therefore, our PKM Untar Team proposes to hold training on the technical process of posting ledgers and preparing balance sheets as extracurricular activities for class XII. This activity will be carried out on Wednesday, November 17, 2021 online using Zoom media. The implementation of this PKM activity includes the presentation of material by the Untar PKM team and then continues with a discussion of the simulation of sample questions and questions and answers. The outputs of this activity are mandatory outcomes in the form of proceedings or journals that will be included in seminars organized by Untar, as well as additional outputs in the form of intellectual property rights regarding learning materials.